2011
DOI: 10.1002/jccs.201190140
|View full text |Cite
|
Sign up to set email alerts
|

Ortho‐carboxylate Effects in Copper‐mediated Nucleophilic Substitution of Halothiophenecarboxylic Acids and Halobenzoic Acids with Sodium Bisulphite

Abstract: Ortho-carboxylate effects in Ullmann type nucleophilic substitution reactions were found to be much more pronounced as compared to those of other substituent and steric factors. In this study, we propose an ortho halogen assisted intramolecular oxidative addition-reductive elimination mechanism that fits our experimental observations. Experimental data has been generated with halothiophenecarboxylic acids and halobenzoic acids by performing copper-mediated nucleophilic substitution with scant referred sodium b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Generally, as seen from the literature review, it could be speculated that Ullmann-type reactions could be possible also for chlorinated CNTs. Nevertheless, verification of this hypothesis would require new extensive studies because CNT–Cl as aryl chlorides counterparts could emerge as inert in the catalytic system and hence must have been replaced by bromides or iodides or have been activated by the presence of electron-withdrawing groups (e.g., carboxylic) [52]. We believe that all the above claims would provide a sound subject for the future comprehensive studies.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, as seen from the literature review, it could be speculated that Ullmann-type reactions could be possible also for chlorinated CNTs. Nevertheless, verification of this hypothesis would require new extensive studies because CNT–Cl as aryl chlorides counterparts could emerge as inert in the catalytic system and hence must have been replaced by bromides or iodides or have been activated by the presence of electron-withdrawing groups (e.g., carboxylic) [52]. We believe that all the above claims would provide a sound subject for the future comprehensive studies.…”
Section: Discussionmentioning
confidence: 99%
“…80 reported an Ullmann-type reaction of halothiophenecarboxylic acids and halobenzoic acid with sodium bisulfite (Scheme 4). The proposed oxidative addition and reductive elimination mechanism were supported by the following observations: 1) The reactivity order ArBr 〉〉 ArCl, and the cyclic voltammetric data on cathodic potential was consistent with the nucleofugicity of the halide; 2) Couplings were favored by the presence of electron-withdrawing groups; 3) Coupling did not occur without a copper catalyst; 4) Radical inhibitors, such as butylated hydroxytoluene (BHT) did not suppress the reaction, and the results showed that ortho -carboxylic acid groups accelerated significantly the rate of oxidative addition process of the copper complex to the C-Br bond.…”
Section: Introductionmentioning
confidence: 99%